Low-dose radiation therapy for COVID-19 pneumopathy: what is the evidence? - Roedel, Franz; Arenas, Meritxell; Ott, Oliver; Fournier, Claudia; Georgakilas, Alexandros G.; Tapio, Soile; Trott, Klaus-Ruediger; Gaipl, Udo (Strahlentherapie und Onkologie, 2020)
In the current dismal situation of the COVID-19 pandemic, effective management of patients with pneumonia and acute respiratory distress syndrome is of vital importance. Due to the current lack of effective pharmacological concepts, this situation has caused interest in (re)considering historical reports on the treatment of patients with low-dose radiation therapy for pneumonia. Although these historical reports are of low-level evidence per se, hampering recommendations for decision-making in the clinical setting, they indicate effectiveness in the dose range between 0.3 and 1 Gy, similar to more recent dose concepts in the treatment of acute and chronic inflammatory/degenerative benign diseases with, e.g., a single dose per fraction of 0.5 Gy. This concise review aims to critically review the evidence for low-dose radiation treatment of COVID-19 pneumopathy and discuss whether it is worth investigating in the present clinical situation.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Anti-inflammatory; COVID-19; Low-dose radiation therapy; Pneumonia; SARS-CoV-2